Proton MR Spectroscopy in Wernicke Encephalopathy - Rugilo, Carlos A. (AJNR Am J Neuroradiol, 2003)
Summary: Wernicke encephalopathy is caused by thiamine deficiency. Although the clinical picture has been well established for some time, clinical diagnosis is attained in only 20% of the cases. MR imaging techniques contribute to early diagnosis of Wernicke encephalopathy. We herein report MR imaging and proton MR spectroscopic findings for a patient with clinical and biochemical features consistent with Wernicke encephalopathy. Increased lactate and typical MR imaging findings are discussed in the context of the known pathophysiology of Wernicke encephalopathy.